Diseminasi Pembuatan Pupuk Organik Cair dari Akar Bambu di Desa Srigading, Lampung Timur - Dedy Prasetyo; Didin Wiharso (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2021)
Land degradation in the rice field is caused by the continuous use of synthetic agrochemicals and low input of organic fertilizers. Assistance and training for farmers are needed to utilize organic fertilizers as additional inputs in cultivation practices. Liquid organic fertilizer (LOB) can be a solution because the making process and application are easier. This dissemination aims to provide knowledge and practice of making LOB from local biological resources such as bamboo roots. The target of the activity are farmers in Srigading, Labuhan Maringgai, East Lampung. The activity was carried out using explanation method and the practice of making LOB from bamboo roots. This activity is carried out for 6 months covering surveys, preparation, delivering materials, practices, and monitoring. The activity was held on August 7, 2021 at the residence of Mr. Tugimin, with a total of 13 participants. The presentation of the material included the importance of soil organic matter for soil health, explanation about LOB, and continued the practice of making LOB. Based on the results of the pretest, the knowledge of farmers about negative impact of using synthetic agrochemicals and the importance of organic matter is still low, so that the explanation can increase farmers' knowledge as indicated by the posttest is increasing from 20% to 86%. Monitoring result showed that the LOB made has been successful with the characteristics like tape smell, but it is still not yet optimal. Farmers also expect follow-up activities for innovation on other organic fertilizers and biofertilizers.